2013
DOI: 10.1111/ijfs.12387
|View full text |Cite
|
Sign up to set email alerts
|

Alginate coatings containing grapefruit essential oil or grapefruit seed extract for grapes preservation

Abstract: International audienceBiodegradable coatings based on 1% and 2% sodium alginate (NaAlg) with and without grapefruit seed extract (GSE) or grapefruit essential oil (GEO) were applied to table grapes to preserve their quality. Changes in weight loss, firmness and antioxidant activity were assessed over 15days of cold storage. The effectiveness of developed coatings to control postharvest decay of inoculated grape berries stored for 5days at 20 degrees C was also investigated. Biodegradable coatings based on pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 34 publications
6
51
1
2
Order By: Relevance
“…The phenolic and flavonoid content alterations are limited by applying edible coatings and consequently, bioactive compounds are accumulated leading to the increased antioxidant activity. Similar to our result, Aloui et al () also showed higher antioxidant activity in table grapes coated with the alginate combining grape seed extract, in comparison with the control, at the end of the storage period. Similar observations have been reported by Takma, and Korel, (), who reported that the alginate coating enriched with vanillin maintained the initial antioxidant activity of grapes stored for 35 days at 4 ± 2°C.…”
Section: Resultssupporting
confidence: 92%
“…The phenolic and flavonoid content alterations are limited by applying edible coatings and consequently, bioactive compounds are accumulated leading to the increased antioxidant activity. Similar to our result, Aloui et al () also showed higher antioxidant activity in table grapes coated with the alginate combining grape seed extract, in comparison with the control, at the end of the storage period. Similar observations have been reported by Takma, and Korel, (), who reported that the alginate coating enriched with vanillin maintained the initial antioxidant activity of grapes stored for 35 days at 4 ± 2°C.…”
Section: Resultssupporting
confidence: 92%
“…Aloui, Licciardello, Khwaldia, Hamdi, and Restuccia () reported antifungal activity of sodium alginate edible coating against Penicillium digitatum in the culture media and then in inoculated Valencia oranges. In another study, Aloui et al () found the efficacy of sodium alginate edible coating in decreasing fungal decay by P. digitatum in the inoculated grapes. They believed that sodium alginate inhibits gaseous exchanges that can lead to reduction of CO 2 accumulation and oxygen permeability and followed by decline of fungi growth in the coated products.…”
Section: Resultsmentioning
confidence: 96%
“…Propolis, a hard and resinous natural product derived by bees from plant juices, exhibits antibacterial activity due to its high flavonoid content (Benhanifia et al, 2013;Burdock, 1998;Kujumgiev et al, 1999). Grapefruit seed extract (GSE), a commercial product derived from the seeds and pulp of grapefruit, also has powerful antimicrobial properties (Lim et al, 2010) mainly due to the polyphenolic compounds it contains (Saito et al, 1998;Aloui et al, 2014). However, to our knowledge, no trial using antimicrobial air filters prepared with shiitake, propolis, and GSE natural products has been previously reported.…”
Section: Introductionmentioning
confidence: 99%